Analisa Penumpang dengan Metode SARIMA (Studi Kasus: Bandar Udara Raja Haji Fisabilillah) - Yayuk Setyaning Astutik (Unisda Journal of Mathematics and Computer Science (UJMC), 2019)
Raja Haji Fisabilillah International Airport is an airport in Tanjungpinang and it is quite high in service levels for the flow of passengers and goods. Based on the data from Airport Quality Angkasa Pura II, the passengers growth has both decreased and increased in the last 3 (three) years. In 2015, there were 258,936 people in total and has decreased to 246,828 people in 2016 and increased again in 2017 by 351,688 people. Therefore, it is necessary to evaluate the terminal of Raja Haji Fisabilillah International Airport. The methods used are observation and forecasting using the SARIMA. The evaluation and analysis results show that the terminal of Raja Haji Fisabilillah International Airport still meets the applicable standards and passenger movements for the next year 2020 indicate that all equipment facilities for the needs of terminal passengers of Raja Haji Fisabilillah International Airport are still adequate.